Ius Migrandi on Central America - Chávez Marín, José Erick (2022)
The aim of this essay is to present the origin and historical evolution of Ius migrandi in Central America. First, it will briefly develop its existence and relevance on roman law, then it will analyze how this way of understanding Ius Migrandi and nationality are somehow transplanted on the 1791 French Constitution and 1812 Cádiz Constitution. Lastly, it will study how these constitutions ideologically influenced this legal institution in this sub-region of Latin America.